Apoptosis induced by farrerol in human gastric cancer SGC-7901 cells through the mitochondrial-mediated pathway. Issue 5 (September 2015) - Liu, Enli; Liang, Taigang; Wang, Xiaojian; Ban, Shurong; Han, Lingge; Li, Qingshan
<x xml:space="preserve">Abstract</x> Farrerol, a typical flavanone isolated from the Chinese medicinal plant Rhododendron dauricum L., has been found to show various biological activities. However, to the best of our knowledge, its inhibitory actions against cancer cells have not been reported as yet. Therefore, the present study aimed to investigate the cytotoxic and apoptotic effects of farrerol on human gastric cancer SGC-7901 cells. Farrerol showed a 50% inhibition of SGC-7901 cell growth at a concentration of 40.4 μmol/l for 24 h according to MTT assays. The cell morphology results indicated that SGC-7901 cells treated with farrerol showed several features of apoptotic cell death, which was also confirmed by the Annexin-V FITC/PI double-staining assay. Further studies showed that farrerol treatment induced the attenuation of mitochondrial membrane potential, accompanied by the release of Cyt-c and the activation of caspase-9 and caspase-3. Furthermore, farrerol decreased the gene expression of Bcl-2, whereas the gene expression level of Bax was found to increase after farrerol treatment. These combined results indicated that farrerol can induce apoptosis through a mitochondrial-mediated pathway.